The influence of electrocoagulation to the reduction of COD, BOD, and TSS of Batik Industry wastewater - Faida Zuhria; Sarto Sarto; Imam Prasetyo (Sustinere: Journal of Environment and Sustainability, 2018)
Despite the positive economic impact of the growing Batik industry in Yogyakarta, wastewater pollution from the dyeing process poses a significant environmental threat. Initial measurements of COD, BOD, and TSS in wastewater from the dyeing process using Naphtolat and Diazo Salts exceeded the regulatory thresholds. Therefore, this study applied electrocoagulation to treat Batik wastewater. The results showed that the electrode spacing and applied voltage significantly affected the reduction of COD, BOD, and TSS in the electrocoagulation process for dye wastewater at the Batik industry "Rara Djonggrang." The optimum electrode spacing for TSS and BOD reduction was 2 cm, achieving an 85.71% decrease in TSS and a 7.02% reduction in BOD. Meanwhile, the optimum COD reduction occurred at a spacing of 4 cm, with a 92.18% decrease. The most effective voltage for reducing TSS and COD was 15 V, leading to an 85.71% TSS decrease and a 92.18% COD reduction. The most effective BOD reduction was achieved using a voltage of 10 V and an electrode spacing of 6 cm. Electrocoagulation using aluminum electrodes was found to be the most suitable method for treating Diazo Salt wastewater.